COMPARISON OF INCIDENCE OF POST-DURAL PUNCTURE HEADACHE IN PATIENTS UNDERGOING SPINAL ANESTHESIA FOLLOWING MEDIAN VS PARAMEDIAN APPROACH - BUTT , MR; JAVED , HM; ASHFAQ , MA; ZAHID , MM; IQBAL , A; KHALID , M (Biological and Clinical Sciences Research Journal, 2023)
Post-Dural Puncture Headache (PDPH) is a common complication after spinal anesthesia, particularly in obstetric populations. The choice of needle insertion technique, either midline or paramedian, may impact the incidence of PDPH. Previous studies have shown conflicting results, necessitating further investigation in specific patient populations. This prospective study aimed to compare the incidence of PDPH between the midline and paramedian approaches. One hundred twenty-two participants were included and divided equally into two groups (Group M and Group P). Patient demographics, including age, body mass index (BMI), gender distribution, type of surgery, and ASA physical status, were recorded. The occurrence of PDPH within the first three postoperative days was assessed and compared between the two groups. The mean age of the study population was 37 ± 9.55 years, with no significant difference between Group M and Group P (p = 0.09). BMI, gender distribution, type of surgery, and ASA physical status also showed no significant differences between the groups.Regarding PDPH incidence, 6.6% of participants in Group M and 4.9% in Group P experienced PDPH. The overall incidence of PDPH in the entire sample was 5.7%. However, the p-value for comparing the occurrence of PDPH between the two groups was 0.698, indicating no statistically significant difference. This study found no significant difference in the incidence of PDPH between the midline and paramedian approaches. These results align with previous studies that have explored the association between needle insertion techniques and PDPH incidence.